Relevansi Pidato Presiden pada KTT D-8 terhadap Diplomasi Indonesia dengan Palestina Perspektif Siyasah Dauliyah - Abdi Dzil Ikram; Idzam Fautanu; Luthfi Fahrul Rizal (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2025)
Abstract: The Palestinian conflict represents a global humanitarian and justice crisis, particularly relevant to Muslim-majority countries. President Prabowo Subianto’s speech at the 2024 D-8 Summit in Cairo serves as a significant diplomatic expression of Indonesia’s support for Palestinian independence. This study aims to analyze the substance of the speech as a form of transformative diplomacy from the perspective of Siyasah Dauliyah (Islamic International Political Jurisprudence). The research employs a normative juridical method with a qualitative approach, based on library research encompassing national law, international law, and Islamic legal-political theory. The findings show that the President’s speech not only has constitutional and international legal legitimacy but also embodies the core values of Siyasah Dauliyah, including justice (‘adl), public benefit (maslahah), Islamic solidarity (ukhuwah Islamiyyah), and equality (musawah). The speech underscores Indonesia’s active diplomatic role as a moral and strategic Islamic actor that advocates not only for humanitarian sympathy but also for collective Muslim action against global injustice. Hence, the speech can be interpreted as an actualization of contemporary Islamic diplomacy that is ethical, legally valid, and strategically significant in the context of the Palestinian struggle. Kewords: Diplomasi; Palestine; Siyasah Dauliyah   Abstrak: Konflik Palestina merupakan isu kemanusiaan global yang mendapat perhatian besar, khususnya dari negara-negara mayoritas Muslim. Pidato Presiden Prabowo Subianto pada Konferensi Tingkat Tinggi (KTT) D-8 tahun 2024 di Kairo menjadi simbol penting dari posisi diplomatik Indonesia dalam mendukung kemerdekaan Palestina. Penelitian ini bertujuan untuk menganalisis substansi pidato tersebut sebagai bentuk diplomasi transformatif dalam perspektif Siyasah Dauliyah. Metode yang digunakan adalah yuridis-normatif dengan pendekatan kualitatif, melalui studi pustaka terhadap sumber hukum nasional, hukum internasional, dan literatur fiqih siyasah. Hasil penelitian menunjukkan bahwa pidato Presiden tidak hanya memiliki legitimasi konstitusional dan hukum internasional, tetapi juga mencerminkan prinsip-prinsip utama dalam Siyasah Dauliyah seperti keadilan, kemaslahatan umat, ukhuwah Islamiyyah, dan persamaan. Pidato ini menegaskan peran aktif Indonesia sebagai aktor diplomatik Islam yang tidak hanya menyuarakan simpati, tetapi juga menyerukan tindakan kolektif umat Islam terhadap ketidakadilan global. Dengan demikian, pidato tersebut dapat dimaknai sebagai aktualisasi diplomasi Islam kontemporer yang etis, sah secara hukum, dan strategis dalam konteks perjuangan Palestina Kata kunci: Diplomasi; Palestina; Siyasah Dauliyah.